Rekonstruksi Pertimbangan Maslahat dalam Pemberian Dispensasi Nikah untuk Meminimalkan Potensi Perceraian - Nursyamsi Ichsan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Marriage dispensation in Indonesia has shown a significant increase and is often used as a legal solution to urgent social problems, such as out-of-wedlock pregnancy. This study aims to analyze maslahah (public interest) considerations in granting marriage dispensations and to reconstruct legal reasoning toward long-term welfare. This research employs a normative legal method with statutory, conceptual, and case approaches, using legal materials obtained through library research. Data analysis is conducted qualitatively through systematic and evaluative interpretation of legal norms. The findings indicate that marriage dispensations are often granted based on pragmatic considerations without adequately assessing the psychological, social, and economic readiness of prospective spouses. As a result, such marriages are prone to instability and may end in divorce. Therefore, it is necessary to reconstruct maslahah-based considerations by integrating maqasid al-shariah principles into judicial reasoning. The implications highlight the need for a paradigm shift in granting marriage dispensations, from a pragmatic approach toward one grounded in long-term welfare. This study recommends strengthening judicial guidelines through multidisciplinary considerations, particularly psychological and social aspects, to ensure decisions support long-term family stability and reduce the risk of divorce.